Modeling of situational management of repair works at oil and gas producing enterprises - Гобир, І. Б. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2014)
A dynamic model of management technical state equipment of oil and gas companies and procedures for improving the management of repair maintenance of main production by establishing a correspondence between the typical operating situations and adopted them in management decisions. Condition of the equipment or its components characterized probabilities of failure, that may have an endless set of values, and the effectiveness of the adopted strategy at some point, appears at some unknown time horizon. The optimality of this solution is measured in terms of projected economic benefit for this and subsequent steps. Optimization criterion is minimum total expenses over the life of the equipment. It is argued that the application of the results obtained in the work can increase the effectiveness of the organization and management of maintenance and repair of equipment oil and gas companies. Introduced in the scientific and methodical approach of the management of repair services for oil and gas companies, based on the principles of situational control, allows you to analyze the impact of the changing trends of the market environment factors on the formation of industrial infrastructure management companies. The studies are universal and can be used for many social and economic systems in order to ensure effective management of repair service.